Unusual Occurrence of Syncytial Epithelia in the Male Accessory Glands of Shore Bugs (Leptopodomorpha in Hemiptera) - Koji Takeda; Jun Yamauchi; Riku Naoi; Tadashi Ishikawa; Takashi Adachi-Yamada (Diversity)
(1) Background: The insect male accessory gland (MAG) produces seminal fluid components crucial for male reproduction, analogous to the mammalian prostate. While some insect MAGs exhibit binucleate epithelial cells for luminal volume plasticity, the diversity of cellular arrangements and their functional implications across insects remain largely unknown. (2) Methods: We investigated the cellular architecture of MAG epithelia in various shore bug species (infraorder Leptopodomorpha, Hemiptera) and their mechanisms of multinucleation and potential MAG volume regulation. (3) Results: The MAG epithelia of shore bugs comprise a small number of large, plastic syncytial cells with varying nuclear numbers. We hypothesize that these syncytia facilitate effective MAG volume expansion post-eclosion. Uniquely, MAG shrinkage involves the localized contraction of limited muscle fibers, unlike the systematic contraction of circular muscles in most other insects. We further describe sequential cell fusion during the nymphal stage as the mechanism of multinucleation. (4) Conclusions: The unique syncytial organization of Leptopodomorpha MAG epithelia represents an evolutionary divergence from typical binucleate or mononucleate structures in other insects; it is likely that this enables distinct mechanisms for reproductive fluid storage and evacuation. This study highlights the evolutionary diversity of male reproductive organ morphology and function within insects.